Video surveillance for fall detection - Ng, Choon Yee. (2013)
A significant growing elders population among developed country like Singapore create more attentions in establish a better healthcare system to safeguard the safety of elders at home. Rising of the computer power enhances the computer vision technique and provide a better solution in detecting falls. In this project, a few image processing technique were used to analyze the human shape deformation and detect falls. Finally falls could be detected through some specification. The results in the project could be improved by further future work recommended in the last section.